Determinants of corporate social responsibility (CSR) attitudes: perspective of travel and tourism managers at world heritage sites. Issue 6 (10th June 2019) - Chi, Christina Geng-qing; Zhang, Chaozhi; Liu, Yuanyuan
Abstract : Purpose: This study aims to examine how tourism impacts on local community, managers' attachment to the community and their identification with the value of heritage resources influence managers' corporate social responsibility (CSR) attitudes, utilizing the value identification and agency theories. Design/methodology/approach: The proposed hypotheses were tested utilizing cross-sectional data collected from 228 managers of a plethora of travel and tourism companies that operate at a UNESCO World Heritage site in China. A structured questionnaire was administered in person in managers' offices by a team of trained research assistants. A total of 202 valid surveys were included in the data analysis. A two-step structural equation modeling (SEM) approach was used to first examine the psychometric properties of the measurement model, and then test the causal relationships proposed in the structural model. Findings: The findings indicate that managers' place attachment, their heritage value identification and their perceptions of positive tourism impacts affect their CSR attitudes. However, the negative effects of tourism do not significantly influence CSR attitudes. Data collected through open-ended questions incorporated in the structured survey have provided justification for the insignificant relationship. Originality/value: CSR perceptions of managers, especially those at heritage sites, have not received much attention from tourism scholars. Because travel and tourism companies at heritage sites are integral in the preservation and conservation of heritage sites while managers of those companies are the ones who initiate and implement socially responsible policies and practices, it is important to understand the factors that may influence those managers' CSR attitudes and behaviors.